The views of the Muslim scholars on the topic of Al-Zihar (International Journal of Psychosocial Rehabilitation, 2020)
Praise is to Allah the Lord of the worlds and May the blessings and peace of Allah be upon the most honored of messengers our master Muhammad and upon all his family and companion. The rule of Al-Zihar is important in Islamic jurisprudence, It is related to family transactions between men and his wife, and it has a great social, psychological impact on social life and its continuity, Therefore, the thought of the Great Prophet and the imams concerned with the detailed statement of the subject of Al-Zihar in order to clarify the four pillars of his rule, as well as the penalty that is imposed on the man before he is on the woman; In order to preserve society and its interdependence, And also in order to protect society from mental and psychological diseases, and gross injustice to the other half of society; Therefore, scholars of religion, Psychologists , educational guidance and others have taken care of the provisions concerning the individual and the family, to provide a healthy and good community, Therefore, the following plan was adopted in this research.